2008
DOI: 10.1149/1.2883827
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Aluminum Hydride in the Anodic Dissolution of Aluminum in Alkaline Solutions

Abstract: The mechanism of anodic alkaline dissolution of aluminum was investigated through the analysis of cyclic voltammetry (CV) and potential step experiments. Attention was focused on the role of aluminum hydride (AlH3) as a reaction intermediate, as suggested by the recent detection of AlH3 formation during open-circuit dissolution. Potential step experiments at pH 11.75 revealed that the potential at the metal–surface film interface was close to the Nernst potential of AlH3 oxidation. This finding suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Such a film if composed of pure alumina would be electrically insulating; thus, direct reduction of Cu 2+ ions by Al could occur only at isolated conductive defects, producing Cu particles rather than the observed thin continuous film. However, the presence of hydride in the surface layer is demonstrated by the present APT results, as well as the electrochemical potential and SIMS measurements discussed above. In solution, this hydride might be in the form of a continuous AlH 3 layer, or interstitial ions such as H – in the oxide. Upon addition of CuSO 4 to the alkaline bath, either type of hydride could reduce cupric ions directly to copper metal, for example 2 AlH 3 + 8 OH + 3 Cu + 2 3 Cu + 2 Al ( OH ) 4 + 3 normalH 2 In experiments with no copper addition, upon emersion of the sample, water vapor or oxygen would oxidize the hydride layer to aluminum oxide or hydroxide, in a reaction such as AlH 3 + 3 2 normalO 2 1 2 Al 2 normalO 3 + 3 2 normalH 2 normalO Thus, the oxide thickness on the alkaline etched sample would be greater than that on the sample with the copper deposit, as is consistent with the APT results Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a film if composed of pure alumina would be electrically insulating; thus, direct reduction of Cu 2+ ions by Al could occur only at isolated conductive defects, producing Cu particles rather than the observed thin continuous film. However, the presence of hydride in the surface layer is demonstrated by the present APT results, as well as the electrochemical potential and SIMS measurements discussed above. In solution, this hydride might be in the form of a continuous AlH 3 layer, or interstitial ions such as H – in the oxide. Upon addition of CuSO 4 to the alkaline bath, either type of hydride could reduce cupric ions directly to copper metal, for example 2 AlH 3 + 8 OH + 3 Cu + 2 3 Cu + 2 Al ( OH ) 4 + 3 normalH 2 In experiments with no copper addition, upon emersion of the sample, water vapor or oxygen would oxidize the hydride layer to aluminum oxide or hydroxide, in a reaction such as AlH 3 + 3 2 normalO 2 1 2 Al 2 normalO 3 + 3 2 normalH 2 normalO Thus, the oxide thickness on the alkaline etched sample would be greater than that on the sample with the copper deposit, as is consistent with the APT results Table .…”
Section: Resultsmentioning
confidence: 99%
“…The films consisted of small particles overlying copper layers of order nanometers in thickness. In the same pH range, electrochemical measurements demonstrated that the Al potential lies close to the Nernst potential determining AlH 3 stability, suggesting the presence of a hydride-containing surface layer on Al. The formation of hydride during alkaline dissolution was detected by secondary ion mass spectrometry (SIMS) . In the copper deposition experiments, QCM and open circuit potential transients revealed a distinct initial stage of deposition occurring near the hydride oxidation potential, in which the mass change was equivalent to a deposited Cu layer of thickness 2–3 nm .…”
Section: Introductionmentioning
confidence: 96%
“…The corrosion rate of aluminium alloys in alkaline solutions varies with time [36], which is particularly evident at the opencircuit potential for aluminium alloys when the changes in the rate of hydrogen evolution exactly mirror the changes in the open-circuit electrode potential with time [37]. Upon immersion, the open-circuit potential of aluminium alloys shifts to a very negative value of À2.0 V vs. Hg/HgO due to the presence of aluminium hydrides [38,39], and possibly hydrides of the alloying elements, creating a hydroxide-free surface and a high rate of hydrogen evolution [37]. Once the alloy surface becomes passivated by a hydroxide layer, its potential shifts more positively, which is accompanied by a reduction in the rate of hydrogen evolution.…”
Section: Evaluating the Electrochemical Behaviour Of Aluminiummentioning
confidence: 99%
“…2) along with observations of timedependent concentrations of metal vacancies detected by PAS and hydride particles found by SIMS and AFM. 2,4 These results indicate chemical pathways to corrosioninduced tensile stress increases and hydride formation, factors that play important roles in SCC mechanisms.…”
mentioning
confidence: 85%